Novel TMC8 splice site mutation in epidermodysplasia verruciformis and review of HPV infections in patients with the disease. (4th August 2017) - Imahorn, E.; Yüksel, Z.; Spoerri, I.; Gürel, G.; Imhof, C.; Saraçoğlu, Z.N.; Koku Aksu, A.E.; Rady, P.L.; Tyring, S.K.; Kempf, W.; Itin, P.H.; Burger, B.
Abstract: Background: Epidermodysplasia verruciformis (EV) is a genodermatosis leading to infections with cutaneous HPV, persistent plane warts and a high rate of non‐melanoma skin cancer (NMSC). Biallelic loss‐of‐function mutations in TMC6 and TMC8 are known to be causative. Objective: The aim of this study was to report EV‐causing mutations in four patients with EV and to give an overview of all described patients with EV. Patients and methods: We investigated four patients with classical features of EV from two families. All patients were affected by plane warts with typical EV histology since early childhood, and β‐HPVs were detected on their skin. One patient had recurring cutaneous squamous cell carcinomas (cSCC) and carcinomas in situ (Bowen type). We sequenced both TMC6/8 for disease‐causing mutations and quantified levels of gene expression. We also performed a systematic literature review to discuss these patients in the context of previously reported cases, mutations already identified, as well as HPV types. Results: Three patients of one family carried a homozygous splice site mutation in TMC8 resulting in aberrantly spliced transcripts that were not degraded. By contrast, no TMC6/8 mutation was detected in the patient from the other family. A systematic literature review revealed 501 described patients with EV. Around 40% of patients with EV analysed for genetic alterations carried no mutation in TMC6/8 . While β‐HPVs were identified in the majority of cases, α‐HPVs were detected in several individuals. Conclusion: The relatively high proportion of EV patients without mutation in TMC6/8 indicates the existence of EV‐causing mutations in additional, presently unknown gene(s). However, a homozygous TMC8 splice site mutation in our patients resulted in aberrant transcripts which cannot retain the healthy phenotype. The literature review revealed that HPV‐5 is the most commonly identified HPV in patients with EV, but HPV‐3, HPV‐14 and HPV‐20 were unexpectedly identified more frequently than HPV‐8.